Response to lead (Pb) treatment of Arabidopsis thaliana seedlings: effect of pretreatment with sodium nitroprusside (SNP) - Phang, Ing Chia (2008)
Plants are regularly exposed to unfavorable conditions that impose stress. Lead (Pb), is one of the major pollutants in the environment that causes serious public health and environmental concern. Increasing levels of lead could also have severe consequences for plants. Plants exposed to lead stress initiate signalling pathway, and make specific changes in cell physiology and metabolism to avoid or tolerate the stress. However, mechanisms to reduce the effects of lead may vary from plant to plant, development stage, and culture medium.